Value Co-Capture in B2B Platforms: A Case Study in the Tavern Sector in South Africa - Mekgwe, Boipelo (University of the Witwatersrand, Johannesburg, 2023)
The focus of the study is on value co-capture in B2B platforms: A case study in the FMCG sector in South Africa. The underlying issue is that small businesses in the FMCG sector are facing competition from established organisations and now require the use of information and technology systems to be competitive. AB InBev therefore created the BEES B2B platform to ensure that tavern owners amongst other businesses utilise technology to meet their aims and objectives. This study aims to determine how value co-creation can be realised by using the BEES application in the operations of tavern owners in the Gauteng Province. The research employed a qualitative approach to capture the opinions and perspectives of participants. The study utilised semi-structured interviews of 12 participants who were purposefully selected and gave consent to be participants. Through deductive thematic analysis as the data analysis method, the study discovered that since the adoption of the BEES application by tavern owners, there has been a perceptible increase in the efficiency of business operations as well as a noticeable achievement in the retention of competitive advantage. This is through utilising features such as browsing to make purchases and review and feedback to ensure the effectiveness of the application. Tavern owners utilising BEES B2B, have enhanced service quality in their operations. From the study, it was discovered that despite the discernible advantages there are also technological challenges with the use of the application due to issues of cyber security and a lack of internet education. This has had an impact on the effective use of the application as most tavern owners are not technologically savvy. The use of the application is also challenging due to a lack of access to the internet by tavern owners. Access to the internet remains a challenge in the developing world as the internet is not equally shared and there are associated charges that impact the effective use of the internet by tavern owners. The use of the BEES platform is also difficult for users because of the complexity of its application. Additionally, the lack of educational qualifications of tavern owners profoundly impacts how they use the application and therefore affects how they comprehend such an important application. This study recommends that AB InBev enhance internet education and skills development for tavern owners. The rationale is that it will ensure that tavern owners understand effectively how they can utilise the application. There is a need to ensure that the application is user-friendly, and the study also advocates that a point system as a reward for the use of the application be utilised.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Value Co-Capture; B2B Platforms; Tavern Sector; South Africa; UCTD; SDG-8: Decent work and economic growth